Catheter-related bloodstream infection caused by Kodamaea ohmeri: A case report and literature review. Issue 6 (June 2017) - Kanno, Yoshiaki; Wakabayashi, Yoshitaka; Ikeda, Mahoko; Tatsuno, Keita; Misawa, Yoshiki; Sato, Tomoaki; Yanagimoto, Shintaro; Okugawa, Shu; Moriya, Kyoji; Yotsuyanagi, Hiroshi
Abstract: Kodamaea ohmeri is a rare yeast pathogen that has recently emerged as an important cause of fungemia in immunocompromised patients. However, appropriate therapy for this infection remains unclear. We report a case of catheter-related blood stream infection caused by K. ohmeri in a 58-year-old patient who improved after removal of the central venous catheter and administration of micafungin. Considering the antibiotic susceptibility of this pathogen and reviewing literature, echinocandins may be the first choice for an empiric therapy for this pathogen.